2013
DOI: 10.1089/jop.2012.0121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autologous Serum on Vitrectomy with Internal Limiting Membrane Peeling for Idiopathic Macular Hole

Abstract: Purpose: We sought to evaluate the effects of intraoperative adjunctive autologous serum in idiopathic fullthickness macular hole surgeries, and to compare the surgical outcomes with a no-serum control group. Methods: In this retrospective, case-control study, 38 consecutive eyes received vitrectomy with internal limiting membrane removal for idiopathic full-thickness macular holes. Two groups were created according to the use of autologous serum. Outcome measures were visual acuity (VA), closure of the macula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…LCFT provided similar outcomes to ILM transplant 17 and inverted flap techniques, 3,18 being useful in long-lasting cases where a greater ILM rigidity might be observed. 19 From our results, the use of LCFT and autologous serum were effective in both idiopathic and refractory 20 Furthermore, it creates a bridge for proliferation of glial cells that fill the hole. Nowadays, in almost all operating rooms, all the components needed for this combined treatment are easily available, LCF is more robust and easier to harvest en-bloc than an ILM flap and other proposed tissues.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…LCFT provided similar outcomes to ILM transplant 17 and inverted flap techniques, 3,18 being useful in long-lasting cases where a greater ILM rigidity might be observed. 19 From our results, the use of LCFT and autologous serum were effective in both idiopathic and refractory 20 Furthermore, it creates a bridge for proliferation of glial cells that fill the hole. Nowadays, in almost all operating rooms, all the components needed for this combined treatment are easily available, LCF is more robust and easier to harvest en-bloc than an ILM flap and other proposed tissues.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the autologous serum contains numerous growth factors that can induce fibrocellular migration, adhesion, and proliferation. 20 Furthermore, it creates a bridge for proliferation of glial cells that fill the hole.…”
Section: Discussionmentioning
confidence: 99%
“…After Kelly and Wendel first described the treatment for full-thickness MHs [ 1 ], surgeons have attempted to further enhance patient outcomes and closure rates by implementing and attempting various modifications to the technique for repair [ 2 , 3 , 4 , 5 , 6 ]. With the modifications of the surgical technique, such as ILM peeling [ 2 , 3 , 4 ], inverted ILM flaps [ 5 , 6 ], autologous serum use [ 32 ], amniotic membrane [ 33 ], and retinal grafts [ 34 ], MH has become a treatable disease with a high anatomical success rate reaching more than 90% [ 7 , 8 ]. Despite these improvements, there is continued debate over whether postoperative posturing is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have been scarce. Recent retrospective studies have found no added benefit of autologous serum to the standard ILM peel [125] and significantly higher rate of MH closure with APC compared to WBC [126]. Finally, APC has also been described in combination with a new technique called ''inversion of the hole margin'' in which glial tissue at the MH margin was scraped centrally, followed by a plug of APC.…”
Section: Autologous Blood Productsmentioning
confidence: 99%